2022
DOI: 10.1097/fbp.0000000000000694
|View full text |Cite
|
Sign up to set email alerts
|

The effects of curcumin in learning and memory impairment associated with hypothyroidism in juvenile rats: the role of nitric oxide, oxidative stress, and brain-derived neurotrophic factor

Abstract: The effect of curcumin (Cur) on cognitive impairment and the possible role of brain tissue oxidative stress, nitric oxide (NO) levels, and brain-derived neurotrophic factor (BDNF) were investigated in juvenile hypothyroid rats. The juvenile rats (21 days old) were allocated into the following groups: (1) control; (2) hypothyroid (0.05% propylthiouracil (PTU) in drinking water); (3–5) hypothyroid-Cur 50, 100, and 150, which in these groups 50, 100, or 150 mg/kg, Cur was orally administered by gavage during 6 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Another study by Jena, Chainy, and Dandapat (2012), exploring antioxidant genes in the renal cortex of PTU‐induced hypothyroid rats found differential modulation by vitamin E and Cur, emphasizing the complex interplay in this region. Ahmadabady et al (2022), demonstrated the neuroprotective role of Cur in juvenile hypothyroidism by reducing oxidative stress parameters and increasing BDNF production. Zhang, Yang, et al (2024) highlighted the effectiveness of in synaptic development under oxidative damage and hypothyroid conditions, emphasizing its potential therapeutic role.…”
Section: Effects Of Curcumin On Thyroid Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by Jena, Chainy, and Dandapat (2012), exploring antioxidant genes in the renal cortex of PTU‐induced hypothyroid rats found differential modulation by vitamin E and Cur, emphasizing the complex interplay in this region. Ahmadabady et al (2022), demonstrated the neuroprotective role of Cur in juvenile hypothyroidism by reducing oxidative stress parameters and increasing BDNF production. Zhang, Yang, et al (2024) highlighted the effectiveness of in synaptic development under oxidative damage and hypothyroid conditions, emphasizing its potential therapeutic role.…”
Section: Effects Of Curcumin On Thyroid Functionmentioning
confidence: 99%
“…In the cerebral cortex and cerebellum under PTU (6-n-propyl-2-thiouracil)induced hypothyroidism, Cur mitigated oxidative stress by modulating SOD expression and activity, displaying region-specific effects(Jena, Anand, et al, 2012). Another study by, exploring antioxidant genes in the renal cortex of PTU-induced hypothyroid rats found differential modulation by vitamin E and Cur, emphasizing the complex interplay in this region Ahmadabady et al (2022),. demonstrated the neuroprotective role of Cur in juvenile hypothyroidism by reducing oxidative stress parameters and increasing BDNF production Zhang, Yang, et al (2024).…”
mentioning
confidence: 99%